2013
DOI: 10.1093/rheumatology/ket219
|View full text |Cite
|
Sign up to set email alerts
|

The arthritis-associated HLA-B*27:05 allele forms more cell surface B27 dimer and free heavy chain ligands for KIR3DL2 than HLA-B*27:09

Abstract: Objectives. HLA-B*27:05 is associated with AS whereas HLA-B*27:09 is not associated. We hypothesized that different interactions with KIR immune receptors could contribute to the difference in disease association between HLA-B*27:05 and HLAB*27:09. Thus, the objective of this study was to compare the formation of β2m-free heavy chain (FHC) including B27 dimers (B272) by HLA-B*27:05 and HLA-B*27:09 and their binding to KIR immunoreceptors.Methods. We studied the formation of HLA-B*27:05 and HLA-B*27:09 heterotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 38 publications
1
36
1
1
Order By: Relevance
“…When ERAP is absent, such peptide presentation to newly synthesized B27 molecules is impaired. This result may contribute to two of the proposed mechanisms whereby HLA-B27 contributes to disease pathogenesis, namely, misfolding of the HC of B27 within the ER, resulting in an unfolded protein response (28) phenomenon; and homodimerization of the B27 HC, leading to altered interaction with NK cells (29,30). These two phenomena associated with B27 may lead to slower transport of a diminished number of mature B27 molecules to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…When ERAP is absent, such peptide presentation to newly synthesized B27 molecules is impaired. This result may contribute to two of the proposed mechanisms whereby HLA-B27 contributes to disease pathogenesis, namely, misfolding of the HC of B27 within the ER, resulting in an unfolded protein response (28) phenomenon; and homodimerization of the B27 HC, leading to altered interaction with NK cells (29,30). These two phenomena associated with B27 may lead to slower transport of a diminished number of mature B27 molecules to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one report highlighted that B*2706, unlike B*2709, expressed the highest surface level of FHC, probably reflecting the poor tapasin dependence during the assembly process which produces more dissociation-prone heterotrimeric complexes [39]. More recently, Cauli and co-workers, using transfected cells, have shown that a higher cell surface FHC expression of B*2705 versus B*2709 could contribute to the differential diseaseassociation [40].…”
Section: Introductionmentioning
confidence: 99%
“…HeLa and C1R cells expressing HLA-B*27 and six mutants at P97 (N97T, N97S, N97V, N97R, N97W and N97D) were generated using lentiviral constructs described previously 17. HeLa and C1R cells expressing HLA-B*7 and its P97 mutants (S97N, S97T and S97D), HeLa and 221 cells expressing HLA-B*51 and its P97 mutants (T97N and T97D) were also generated using lentiviruses.…”
Section: Methodsmentioning
confidence: 99%